Development of a Menu Introduction Application for Domino's Pizza Serang Using Construct 2 - Abdul Halim; Ali Rohman; Naswa Cika Ananda (ARRUS Journal of Engineering and Technology, 2025)
The development of information technology has had a significant impact on various aspects of life, including the culinary field. Domino’s Pizza, as one of the international fast-food restaurant franchises, offers a wide variety of menu items that need to be introduced effectively to customers. However, the menu introduction media used so far is still conventional, such as brochures and verbal explanations, which are considered less engaging and interactive. This study aims to develop a menu introduction application for Domino’s Pizza Serang using Construct 2 as an interactive multimedia-based tool. The development method used in this study is the Multimedia Development Life Cycle (MDLC), which consists of the stages: concept, design, material collecting, assembly, testing, and distribution. The application includes several main features, such as the main menu, menu list, and company profile. Application testing was conducted by distributing questionnaires to 10 respondents using the Likert scale. The evaluation results showed that the application received an average user satisfaction score of 4.29 out of 5, indicating that the application is considered good and suitable for use as a promotional and product information medium. Therefore, this application can be an effective solution in introducing Domino’s Pizza products in an engaging and efficient manner.